2008
DOI: 10.1007/s00464-008-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted ileocolectomy in patients with Crohn’s disease: a study of 50 consecutive patients

Abstract: The laparoscopically assisted approach to ileocolic Crohn's disease seems to be feasible and safe, with acceptable immediate postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other early prospective studies comparing laparoscopic assisted with open ileocecectomies in this patient population have yielded similar results. [7][8][9][10] More recent series evaluating laparoscopic ileocolic resection have reflected an increasing comfort of surgeons with laparoscopic surgery. Chaudhary and colleagues 11 reported on 29 patient undergoing primary laparoscopic resection of ileocolic Crohn's disease and found a mean operative time 85 minutes with a mean length of stay of three days.…”
Section: Discussionmentioning
confidence: 99%
“…Other early prospective studies comparing laparoscopic assisted with open ileocecectomies in this patient population have yielded similar results. [7][8][9][10] More recent series evaluating laparoscopic ileocolic resection have reflected an increasing comfort of surgeons with laparoscopic surgery. Chaudhary and colleagues 11 reported on 29 patient undergoing primary laparoscopic resection of ileocolic Crohn's disease and found a mean operative time 85 minutes with a mean length of stay of three days.…”
Section: Discussionmentioning
confidence: 99%
“…17 Accordingly, in this study, patients who had a laparoscopic procedure were less likely to develop an OSI. A large, recent retrospective review of 434 CD ileocolectomy patients found that those with perforating disease were less likely to undergo a laparoscopic procedure and more likely to develop a postoperative leak or abscess than those with stricturing or inflammatory disease.…”
Section: Operative Risk Factors For Organ Space Infectionmentioning
confidence: 95%